2013
DOI: 10.17221/396/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking methods on total phenolic and carotenoid amounts and DPPH radical scavenging activity of fresh and frozen sweet corn (Zea mays) kernels

Abstract: Song J.-F., Liu C.-Q., Li D.-J., Meng L.-L. (2013): Effect of cooking methods on total phenolic and carotenoid amounts and DPPH radical scavenging activity of fresh and frozen sweet corn (Zea mays) kernels. Czech J. Food Sci., 31: 607-612.We evaluated the effect of three different cooking methods on antioxidant content and radical scavenging activity of sweet corn. Both fresh and frozen sweet corn kernels were boiled, microwaved, and stir-fried for 1, 3, and 5 min, respectively, then total phenolic (TP) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…The germination conditions between light and dark periods have been also found to affect the morphological structures, biochemical and phytochemical composition, and antioxidant activity of corn sprouts [70]. The storage conditions, processing techniques, and cooking methods have been also found to affect the phytochemical content and free radical-scavenging activity of maize [21,71]. Recently, studies in our laboratory have shown that high-dose gamma irradiation results in a decrease in antioxidant properties of corn flour [72].…”
Section: Factors Affecting the Phytochemical Profile And Antioxidant mentioning
confidence: 99%
“…The germination conditions between light and dark periods have been also found to affect the morphological structures, biochemical and phytochemical composition, and antioxidant activity of corn sprouts [70]. The storage conditions, processing techniques, and cooking methods have been also found to affect the phytochemical content and free radical-scavenging activity of maize [21,71]. Recently, studies in our laboratory have shown that high-dose gamma irradiation results in a decrease in antioxidant properties of corn flour [72].…”
Section: Factors Affecting the Phytochemical Profile And Antioxidant mentioning
confidence: 99%
“…The antioxidant activities of phenolics and flavonoids have been shown to be a result of their regulation on PGE2 synthesis and inhibition on the expression of NF-κB gene [ 6 ]. It is accepted that fruits and vegetables are rich in bioactive nutrients; for instance, sweet corn contains a number of phytochemicals, as well as dietary fiber, protein, and carbohydrates [ 7 ]. Plant-based foods have been shown to provide benefits in preventing consumers from chronic diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet corn is an abundant vegetable in China and consumed daily for its nutritional value, including phytochemicals and antioxidant properties [ 7 ]. It is widely planted in East China [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of melanoidins during baking further increased the radical scavenging ability of composite tortillas. In addition, the increase in DPPH activity of composite tortillas could be attributed to the heat during baking which contributed to bioactive compounds such as ferulic acid from matric interacting with some antioxidant substances that were dissolved in water during dough formation [47]. A higher DPPH value is related to stronger antioxidant activity and a lower value is associated with a weaker antioxidant activity.…”
Section: Polyphenolic Compounds and Antioxidant Activities Of Maize-bmentioning
confidence: 99%